THE PLIOCENE OF THE PONTIC-CASPIAN REGION AND ITS CORRELATION - Zubakov V.A. (My University, 2000)
Relationships between traditional Pontic-Caspian Pliocene units (Pontian, Kimmerian, and Kuyalnikian regional stages of the Black Sea region and Pontian and Akchagylian regional stages of the Caspian region) and the Messinian, Zanclean, Piacenzian, and Gelasian stages of the Mediterranean are considered. The ranges and boundaries of the units are shown to be inconsistent. It is concluded that the regional Pontic-Caspian type boundaries maximum correlative to those of the standard Mediterranean scale and, consequently, new regional stages should be introduced for the Pontic-Caspian region. It is proposed to change the Pontian boundaries and introduce new regional units: Panagian (= Eoakchagylian), Polovetsian (= Akchagylian s. str.), and Polivadinian stages with their boundaries correlated to geomagnetic field reversals and dated back to 7.2, 5.2, 3.5, and 2.5 Ma, respectively.
Keywords: Pliocene; Cenozoic::Neogene::Pliocene; Кайнозой::Неоген::Плиоцен